Contrasting tree-cover loss and subsequent land cover in two neotropical forest regions: sample-based assessment of the Mexican Yucatán and Argentine Chaco. Issue 6 (2nd November 2018) - Krylov, Alexander; Steininger, Marc K.; Hansen, Matthew C.; Potapov, Peter V.; Stehman, Stephen V.; Gost, Allison; Noel, Jacob; Talero Ramirez, Yamile; Tyukavina, Alexandra; Di Bella, Carlos M.; Ellis, Edward A.; Ellis, Peter
ABSTRACT: The neotropical-forest's northern and southern extremes, covering the Mexican Yucatán and the Argentine Chaco, have among the highest rates of recent tree-cover loss in the biome. This study contrasts the character of loss in these regions, estimating proportions of types of loss and subsequent land cover. It is based on two-stage probability sampling design and field and satellite-image surveys. All estimates include uncertainties, which could be further reduced via model-assisted estimation or additional sampling. This approach can be replicated in other regions to estimate types of loss and associated land cover from a definitive, in-situ perspective. The character of loss in the two areas differed greatly. That in the Yucatán was 54% temporary, mostly under fallow or selectively logged, while that in the Chaco was 85% permanent, split nearly equally between crops and pasture. These data contribute to a quantitative basis for studies of socio-economic drivers of neotropical deforestation.